The Effect of Competence and Compensation on Employee Performance at the Amandraya Community Health Center, Mediated by Job Satisfaction - Laia, Ariston; Halawa, Odaligoziduhu; Bate'e, Maria Magdalena; Telaumbanua, Eliagus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research is motivated by the crucial role of employee performance in achieving organizational goals, particularly in the health sector. Initial observations revealed that the performance of employees at the Amandraya Community Health Center was suboptimal, potentially due to low job satisfaction. This study aims to examine the influence of competence and compensation on employee performance, with job satisfaction as a mediating variable, and to provide recommendations for managerial improvement. The study also seeks to identify factors contributing to job satisfaction to better understand the relationship between competence, compensation, and performance. The research employs a quantitative method, with data collected via questionnaires distributed to 64 employees. The analysis results indicate a positive and significant relationship between competence and performance, as well as between compensation and performance. Employees with higher competence and those receiving fair, adequate compensation tend to be more motivated and productive. Job satisfaction was found to mediate the relationship between competence and compensation on performance, suggesting that creating a supportive work environment, enhancing competence, and improving compensation systems can boost both job satisfaction and performance. The findings highlight the need for effective management of competence and compensation while giving attention to job satisfaction to improve overall employee performance at the Amandraya Community Health Center.